Keratomycosis due to Purpureocillium lilacinum: A case report from Sub-Himalayan region of Uttarakhand - Deepak Juyal (Indian Journal of Pathology and Microbiology, 2018)
The fungus Purpureocillium lilacinum previously known as Paceliomyces lilacinus is an emerging pathogen that can cause severe human infections including devastating oculomycosis. Treatment with traditional antifungals often fails, and the organism shows variable susceptibility to novel triazoles. We hereby report a case of keratomycosis caused by Pur. lilacinum in an immunocompetent male patient following trauma. The patient was successfully treated with voriconazole. The drug shows good activity against Pur. lilacinum and could be a promising therapeutic alternative to treat infections caused by this fungus, which generally shows resistance to conventional antifungal agents including novel triazoles.